First record of the rain frog Pristimantis myersi (Goin & Cochran, 1963) (Anura, Craugastoridae) for Ecuador - Rojas-Runjaic, Fernando J. M.; Rojas-Runjaic, Fernando J. M.; J. M. Guayasamin,; J. M. Guayasamin, (Check List, 2015)
Pristimantis myersi is a small Andean frog that in- habits paramos, sub-paramos and upper Andean forests at elevations between 2,900–3,275 m. It is known from about a dozen localities in the southern end of the Cordillera Central of the Colombian Andes. Herein, we report for the first time the presence of this species in Ecuador, based on ten speci- mens from three localities in the provinces of Imbabura and Sucumbíos. The species’ range is extended and a distribution map with the Ecuadorian records is provided.
Centro Jambatu - ID 1507